2014
DOI: 10.1002/eji.201344200
|View full text |Cite
|
Sign up to set email alerts
|

Granulocytic myeloid derived suppressor cells expand in human pregnancy and modulate T‐cell responses

Abstract: Immune tolerance toward the semiallogeneic fetus plays a crucial role in the maintenance of pregnancy. Myeloid-derived suppressor cells (MDSCs) are innate immune cells characterized by their ability to modulate T-cell responses. Recently, we showed that MDSCs accumulate in cord blood of healthy newborns, yet their role in materno-fetal tolerance remained elusive. In the present study, we demonstrate that MDSCs with a granulocytic phenotype (GR-MDSCs) are highly increased in the peripheral blood of healthy preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
141
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 141 publications
(160 citation statements)
references
References 49 publications
(75 reference statements)
11
141
2
2
Order By: Relevance
“…The heterogeneous phenotype of plaGR-MDSCs and cord blood GR-MDSCs confirms observations from others that GR-MDSCs are a heterogeneous cell population containing different developmental states and that the expression of surface markers strongly depends on environmental factors (14,20,23).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The heterogeneous phenotype of plaGR-MDSCs and cord blood GR-MDSCs confirms observations from others that GR-MDSCs are a heterogeneous cell population containing different developmental states and that the expression of surface markers strongly depends on environmental factors (14,20,23).…”
Section: Discussionsupporting
confidence: 86%
“…The current state of knowledge is that MDSCs are a heterogeneous population of myeloid progenitor cells that can be subdivided at least into a GR-MDSC and a monocytic MDSC subset. In our previous study we found an increase in GR-MDSCs in peripheral blood of pregnant women whereas numbers of monocytic MDSCs were similar in pregnant and nonpregnant women (23). In the present study, we therefore focused on GR-MDSCs.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…CD14 1 HLA-DR 2/low cells, a subset of CD14 1 myelomonocytic cells, exhibit potent suppressive activity 6 , and these cells are monocytic myeloid-derived suppressor cells (MOMDSCs) 7,8 , which have emerged as key immune modulators orchestrating lymphocyte responses. There is increasing interest in the role of MDSCs as tolerance-inducing cells during pregnancy 9,10 . Although studies have suggested that isolated myeloid cells or MDSCs from the peripheral blood of pregnant women could efficiently suppress T-cell proliferation, information concerning the mechanisms governing MDSCs mobilization, particularly during the implantation and invasion of trophoblast cells, is lacking.…”
Section: Introductionmentioning
confidence: 99%